Tuberculosis Treatment Outcomes in Europe: Based on Treatment Completion, Not Cure - Dedicoat, Martin J.; Günther, Gunar; Crudu, Valeriu; Duarte, Raquel; Gualano, Gina; Magis-Escurra, Cecile; Rumetshofer, Rudolf; Skrahina, Alena; Spinu, Victor; Tiberi, Simon; Viiklepp, Piret; van Leth, Frank; et al. (American journal of respiratory and critical care medicine, 2017)
According to the World Health Organization (WHO), successful treatment outcome from pulmonary TB includes patients who meet the criteria for cure and treatment completion (1). [...]WHO-defined definitions for cure and failure in patients with non-MDR-TB are frequently not met in many European countries, as necessary investigations are not performed. Martin J. Dedicoat· Heart of England Foundation Trust Birmingham, United Kingdom and University of Warwick Coventry, United Kingdom Gunar Gunther· Research Center Borstel Borstel, Germany and University of Namibia School of Medicine Windhoek, Namibia Valeriu Crudu Institute of Phthisiopneumology Chisinau, Republic of Moldova and National TB Reference Laboratory Chisinau, Republic of Moldova Raquel Duarte Porto University Porto, Portugal Gina Gualano National Institute for Infectious Diseases "L, Spallanzani" Rome, Italy Cecile Magis-Escurra Radboud University Medical Centre Nijmegen/Groesbeek, the Netherlands Rudolf Rumetshofer Otto Wagner Hospital Vienna, Austria Alena Skrahina Republican Research and Practical Centre for Pulmonology and Tuberculosis Minsk, Belarus Victor Spinu Marius-Nasta-Institut Bucharest, Romania Simon Tiberi AOVV E. Morelli Reference Hospital for MDR and HIV-TB Sondalo, Italy and Barts Health NHS Trust London, United Kingdom Piret Viiklepp National Institute for Health Development Tallinn, Estonia Frank van Leth· University of Amsterdam Amsterdam, the Netherlands and Amsterdam Institute for Global Health and Development Amsterdam, the Netherlands Christoph Lange· Research Center Borstel Borstel, Germany German Center for Infection Research (DZIF) Borstel, Germany University of Lubeck Lubeck, Germany and Karolínska Institute Stockholm, Sweden for TBNET4 *M.J.D., G.G., F.v.L., and C.L. contributed equally to this work. Additional collaborators of the TBNET MDR-TB hospital collaboration are (in alphabetical order): Sofia Alexandru, Institute of Phthisiopneumology, Chisinau, Republic of Moldova; Neus Altet, Unitat de Tuberculosis Vall d'Hebron-Drassanes, DOTS clinic "Servicios Clinicos," Barcelona, Spain; Korkut Avsar, Asklepios Klinik Gauting, Gauting, Germany; Didi Bang, Statens Serum Institut, Copenhagen, Denmark; Raisa Barbuta, Balti Municipal Hospital, Balti, Republic of Moldova; Graham Bothamley, Homerton University Hospital, London, United Kingdom; Ana Ciobanu, Institute of Phthisiopneumology, Chisinau, Republic of Moldova; Manfred Danilovits, Tartu University Lung Hospital, Tartu, Estonia; Heinke Kunst, Heart of England Foundation Trust, Birmingham, United Kingdom, and Queen Mary University, London, United Kingdom; Wiel de Lange, University Medical Center Groningen, Groningen, the Netherlands; Vaira Leimane, Riga East University Hospital, Riga, Latvia; Anne-Marie McLaughlin, St James's Hospital, Dublin, Ireland; Inge Muylle, University Medical Center St. Pieter, Brussels, Belgium; Veronika Polcova, Thomayer University Hospital, Prague, Czech Republic; Cristina Popa, Marius-Nasta-Institut, Bucharest, Romania; and Varvara Solodovnikova, Republican Research and Practical Centre for Pulmonology and Tuberculosis, Minsk, Belarus.